(untitled) (Studia austriaca, 2023)
This paper investigates home videos made by Hojda Stojka, the son of Ceija Stojka (1933-2013), artist and survivor of Auschwitz, Ravensbrück, and Bergen-Belsen. Based on a close reading of significant video sequences, a narrative interview with the videographer, and Ceija Stojka’s publications and films, it analyses how the auto/biographical videos relate to the persecution of the parents’ generation. The paper focuses on the importance of spaces like kitchens, cars and stages, on the value assigned to auto/biographical audiovisual recordings, and the recontextualization and integration of photographs and television recordings into the family memory.